Yitzkah Arad. Gheto in flames. The struggle and destruction of the Jews in Vilno in the holoceust. - Jerusalen, 1980. - 500 p. Rec. Algirdas Jakubčionis. Kitoje ribos pusėje - Jakubčionis, Algirdas (Lietuvos istorijos studijos, 1996)
-